Requirements of technical expertise in the Social Enterprise and Economic Development (SEED) programme - Kassim Buhiran (2011)
Technical knowledge advise has convinced the farmers on their's benefit from the Social Enterprise and Economic Development (SEED) program 201. Most of the 12 farmers with fertigation of chili project were lacking in the knowledge of fertigation and croping schedule. Fertigation should be applied during the day to optimize the photosynthesis potential of the crop to maximize the chili yield, do not fertigate in the evening. Since the chili was planted under the plastic rain-shelter, the maximum production of chilli has to coincide with the wet monson season of October until end of December when chili production outside is imposible and the price of chili is double. The catfish farming activities could be expended through the expension of spawning activity and the production of fish pelet. The facilities for the hatchery system has to be improved by using fibre tanks for the spawing process and better fencing system around the nursery pols to prevent the predators from invading the pols. This improvement wil increase the catfish harvest, reduce the operational cost and sustain the income. For tradisional cake busines, the techical knowledge requirements were mainly on production facilities and ingredients to achieve the standard of GMP and halal certification. Better packaging and branding wil improve the daily sale outside the festive season to sustain the income